G212 Where does the time go?: Real time A&E in-situ simulation to assess protocol adherence and human factors in the emergency management of paediatric convulsive status epilepticus across Yorkshire and the Humber. (27th April 2016) - Motaleb, F; Vas, C; Blythe, J; Perring, K; Hancock, S
Abstract : Aims: In 2013 a retrospective one-year audit of patients admitted to a tertiary paediatric ICU from Yorkshire/Humber hospitals for convulsive status epilepticus (CSE) following rapid sequence induction (RSI) demonstrated that of 23 patients: 9 (40%) had delay in receiving benzodiazepines (BDZ)/Phenytoin and RSI 5 (21%) had received inadequate/excessive BDZ These reasons for inappropriate management are recognised in current literature. However they are limited in their explanation based on prospective studies to date. We hypothesise that human factors, plus deficiencies in clinical knowledge/training are responsible. Methods: Real time A&E in-situ simulation of a standardised paediatric CSE scenario requiring RSI was carried out over several hospitals in the Yorkshire and the Humber. Participants from A&E, Paediatrics and Anaesthetics were blinded to the scenario. By direct observation and debriefing of the simulation the following were analysed: Adherence to the local hospital pathway of CSE emergency management Human factors (assessed by validated NOTECHS rating scale of "very poor" to "very good") Results: In-situ simulations in five A&E departments (two at tertiary children's hospital) have been completed. Median time to first and second BDZ was 8 and 16.5 min (gold standard 5 and 15 min respectively) with no inadequate/excessive BDZ use. Median time to Phenytoin was 27 min (gold standard 25 min) but two simulations highlighted lack of knowledge in Phenytoin preparation, resulting in delayed administration at 37 and 38 min respectively. Three simulations demonstrated inappropriate RSI prior to Phenytoin administration, with each decision to do so linked to human factors issues. An example included steep authority gradient, with the Anaesthetic Consultant stating intubation before Phenytoin should occur and this incorrect decision was not questioned. Yet during debriefing the Paediatric doctors disagreed with this decision but felt they could not speak up against the Anaesthetist at the time. Other human factors issues included "poor" leadership, "poor" situational awareness, "poor" communication and task overloading of team members. However risk anticipation was "good". Conclusion: These simulations provide prospective evidence of management errors in paediatric CSE across the region, with identified reasons for failure consistent with our hypothesis. As such we plan to create targeted regional training programs (e.g. human factors workshops) with the plan to repeat the simulations after implementation.